Detection and phylogenetic characterization of arbovirus dual-infections among persons during a chikungunya fever outbreak, Haiti 2014 - White, Sarah K.; Mavian, Carla; Elbadry, Maha A.; Beau De Rochars, Valery Madsen; Paisie, Taylor; Telisma, Taina; Salemi, Marco; Lednicky, John A.; Morris, J. Glenn, Jr. (PLOS Neglected Tropical Diseases, 2018)
Author summary Chikungunya virus (CHIKV) was the cause of a major epidemic in Haiti from May through August, 2014, as the disease swept through the Caribbean and South and Central America. During the time-period of the epidemic, our group was monitoring a cohort of children in semi-rural Haiti, using molecular and virology methods to assess the etiology of acute undifferentiated febrile illness. We identified CHIKV infections in 82 of 100 children presenting with fever during this time-period; six of the children infected with CHIKV were found to be co-infected with Zika virus (ZIKV), one with Dengue virus serotype 2, and one with Mayaro virus. For the CHIKV and ZIKV infections, a molecular clock calibrated framework revealed results suggestive of simultaneous co-infection. Our data highlight the frequency of dual infections in arbovirus disease cases (with the possibility of simultaneous co-infection), and document the frequent movement of virus strains within the Caribbean and the American continents.